Pulsed Doppler echocardiographic indices for assessing mitral regurgitation. - Veyrat, C (1984)
Pulsed Doppler indices were devised in order to grade the severity of mitral regurgitation on a quantitative basis. Indices were obtained by mapping the regurgitant jet by recording abnormal systolic Doppler signals detected on a "yes/no" basis using a 3 MHz pulsed Doppler velocimeter associated with a cross sectional real time ultrasonic scanner. Combined information from two echographic planes was used to take into account the geometrical three dimensional configuration of the jet. The following dimensions of the jet were measured: (a) the length and the height in the long axis view of the left atrium (long axis regurgitant index (LARI), 0.5 X length X height); (b) the width at the annulus in the short axis view (short axis regurgitant index (SARI); (c) the total regurgitant index (TRI) calculated as the product of LARI multiplied by SARI. Sixteen normal subjects and 94 patients including 46 cases of mitral regurgitation confirmed by angiography (32 of whom proceeded to surgery) were investigated. The diagnostic sensitivity was 91% and the specificity 94%. The jet was detected in 76% of cases. Indices were correlated with independently performed angiographic grading on a three point scale. The best linear correlation was obtained for the TRI; mean values were significantly increased for each grade of severity. Correlations with invasive procedures showed an 87% success rate for the Doppler prediction of the involved regurgitant leaflet(s) and of the anatomical site of the lesion at the annulus. In addition, an abnormal diastolic signal was found in five of the eight patients with ruptured chordae and also a decreased percentage of systolic shortening of the annulus diameter in patients with mitral regurgitation compared with those without.